Current Status and Future Directions of Bone Trauma Surgery (MDPI - Multidisciplinary Digital Publishing Institute, 2025)
The field of bone trauma surgery and bone regeneration is constantly evolving, driven by ongoing advancements in medical technology, surgical techniques, and a deeper understanding of the biological processes involved in bone healing and regeneration. In response to these developments, this reprint of the Special Issue in Medicina titled “Current Status and Future Directions of Bone Trauma Surgery” is dedicated to showcasing the latest insights and exploring future trends in this area. This reprint includes thirteen articles covering all aspects of bone trauma surgery and regeneration, including improvements on current trauma management techniques. Moreover, it aims to offer comprehensive reviews that are practical and applicable to everyday traumatology practice.